Analyzing activity and injury risk in elite curling athletes: seven workload monitoring metrics from session-RPE - Wu, Junqi; Zhao, Fan; Li, Chunlei (Frontiers in Public Health, 2024)
The aim of the study was to compare the differences in the performance of seven Session-Rating of Perceived Exertion-derived metrics (coupled & uncoupled Acute: Chronic Workload Ratio, weekly ratio of workload change, monotony, standard deviation of weekly workload change, Exponentially Weighted Moving Average, and Robust Exponential Decreasing Index) in classifying the performance of an injury prediction model after taking into account the time-series (no latency, 5-day latency, and 10-day latency).The study documented the Rating of Perceived Exertion of eight curlers in their daily training routine for 211 days prior to the Olympic Games.Seven Session-RPE-derived metrics were used to build models at three time-series nodes using logistic regression and multilayer perceptron, Receiver Operating Characteristic plots were plotted to evaluate the model performance.RESULTS: Among the seven Session-RPE-derived metrics multilayer perceptron models, the model without time delay (same-day load corresponding to same-day injury) exhibited the highest average classification performance (86.5%, AUC=0.773). EMWA and REDI demonstrated the best classification performance (84.4%, p<0.001). Notably, EMWA achieved the highest classifying accuracy in the no-delay time series (90.0%, AUC=0.899), followed by the weekly load change rate under the 5-day delay time series (88.9%, AUC=0.841).EWMA without delay is a more sensitive indicator for detecting injury risk.